Ethnomedicinal survey of the plants used for gynecological disorders by the indigenous community of District Buner, Pakistan - Jan, Hammad Ahmad; Jan, Samin; Bussmann, Rainer W; Ahmad, Latif; Wali, Sher; Ahmad, Nadeem (Ethnobotany Research and Applications, 2020)
Background: This study is the first of its own kind conducted in the study area with the aim to document and conserve the indigenous traditional knowledge of medicinal plants used for curing gynecological diseases. Materials and Methods: During the course of work, the use of medicinal plants and their ethnomedicinal uses for gynecological problems were documented by interviewing 532 people of different ages (20-110 years) through semi-structured interviews Results: The result of the present work is showing the dependency of the indigenous population on medicinal plants. In the present work 60 plants, species belonging to 40 families were collected and their medicinal uses were documented by interviewing both genders of the local population through semi-structured interviews and open-ended questionnaires. The results of the study were compared to 14 previously published articles. The result of this study indicates that Asteraceae was the dominant family with 4 species. Similarly, the dominant life form was herb (39 species) and the most used plant part was leaf (19 species). The highest RCF (Relative Citation Frequency) value was obtained for Acacia modesta Wall. 0.71. The highest UV (Use Value) was 0.91 for Trachyspermum ammi (L.) sprague and lowest UV was 0.50 for Ficus benghalensis L. The highest ICF (Informants Consensus Factor) value 1.0 was obtained for emmenagogue and vomiting and the lowest for leucorrhoea (0.67). Conclusions: The present study shows that the study area is rich in ethnomedicinal knowledge. The result also indicates that the local population is more sensitive and careful about gynecological diseases. This study is providing a baseline for future pharmacological studies to discover new herbal drugs. Keywords: Traditional knowledge conservation; Ethno-medicine; Gynecological disorders; Buner; Pakistan